IDE600 : Degree project I / College of Creative Arts - UiTM, College of Creative Arts (Universiti Teknologi MARA (UiTM), 2023)
This course aims to prepare students for developing their understanding in Industrial Design Research and Development. This course will give students capability to apply their knowledge in design & Research Methodology to understand the needs of user in terms of design performance, usability, manufacture and commercial values. The course is designed to supervise student develop their Final Degree Project proposal and integrating them with their Project Report as to fulfill their academic writing course. At this semester, the programme department will appoint Final Design and Project Report supervisor to assist them focusing on any Industrial design selected area topic such as kids, aged and disabled products, household appliances, mobile communication product, contract furniture, office and commercial furniture, outdoor furniture, boat and yachts design, automotive, aircrafts and commercial transport.